Theorizing College Governance Across Epistemic Differences: Awareness Contexts of College Administrators and Faculty - Muzzin, Linda (Canadian Journal of Higher Education, 2016)
To provide a fresh perspective on governance in Canada’s colleges, interview data from administrators and faculty were interpreted through the lens of Glaser and Strauss’ (1965) theoretical categories describing interaction between physicians and patients. An example of a “closed awareness context” is suggested around college fund-raising, while “mutual suspicion” was observed in administrator-faculty interaction around student success policy. Examples of “mutual pretense” include feigned administrator-faculty cooperation around changing college missions and faculty workload formulae. “Open awareness” or dialogue, however, occurred where professional bodies or unions intervened. Awareness contexts are central to symbolic interactionist research, which focusses on how everyday realities are constructed. Similarities between doctor-patient and administrator-faculty interactions can be seen in the examples here. For example, just as doctors feared that delivering bad news to patients might precipitate “mayhem” in the hospital, college administrators may fear that openness around divisive topics might precipitate “mayhem” in college management.